Analysis of the Accuracy of Diagnosis Codes on the Return of BPJS Claim Files at TNI-AD Bhirawa Bhakti Hospital Malang: Analisis Keakuratan Kode Diagnosis Terhadap Pengembalian Berkas Klaim BPJS di RS TNI-AD Bhirawa Bhakti Malang - Bella Artamevia, Fifi; Akbar, Prima Soultoni; Nurhadi, Nurhadi (JOURNAL OF MEDICAL AND HEALTH SCIENCE, 2024)
Coding accuracy is the accuracy and suitability of codes for both diagnoses and actions carried out by coding officers based on applicable provisions, namely ICD 10 version 2010 and ICD 9 CM. The accuracy of diagnostic data is very important in the field of clinical data management, BPJS health billing, and other issues related to health services. said to be accurate, if the files (Individual Patient Report, Coding Confirmation, Supporting Report, medical resume, and operation report) are consistent with each other. It is said to be inaccurate if one or several files do not show consistency. The aim of this research is to determine the analysis of the accuracy of diagnosis codes on the return of BPJS claim files at the TNI-AD Bhirawa Bhakti Hospital, Malang. The type of research used is quantitative, collecting data through interviews. The research subjects were 45 medical records. The research results show that the average return of claim files is 12% of the total claim files submitted each month. The return of claim files was due to the coding officer's lack of understanding of coding rules, incomplete files, the coding officer's background not meeting medical recorder competency standards and the absence of regular meetings related to coding training being held. From the results of this research, it can be concluded that there is a return of claim files due to incompleteness and carelessness of officers. Based on this conclusion, the author suggests holding regular meetings to discuss the accuracy of codification and completeness of medical records as well as additional human resources so that hospitals can minimize refunds of claim costs by parties. BPJS Health. Suggestions for future researchers, when this suggestion is implemented by hospitals, will there be a good influence on the accuracy of the codification and claims return process by BPJS Health.